Scope of social security for the artisan sector in Mexico - Hernández, Linda Lizbett Hernández; Prats, German Martinez; Hernandez, Francisca Silva (IJRDO - Journal of Social Science and Humanities Research, 2021)
Crafts are an important symbol for society as they reflect historical aspects, social and cultural values ​​for artisan communities, in addition to reviving and boosting the family and community economy, reasons for which it is considered important recognize those who are dedicated to the development of these pieces that allow the permanence of trades of ancient origin in our country. Social security is also an important issue for the artisan community, leading a better quality of life for them and their dependents. In Mexico, the National Fund for the Promotion of Handicrafts (FONART) is in charge of providing aid to this sector with the aim of reducing the incidence of diseases and accidents derived from artisanal activity, as well as the interest of promoting a style of healthy living and work environments. Social Security is a term that refers to the well-being of citizens, members of a community, according to the International Labor Organization defines it as the protection that society provides to its members, through a series of public measures, against deprivation economic and social that, if not, would cause the disappearance or a strong reduction in income due to illness, maternity, work accident, or occupational disease, unemployment, disability, old age and death; and also protection in the form of medical assistance and aid to families with children.